Contrasting between‐ and within‐individual trait effects on mortality risk in a long‐lived seabird. Issue 1 (1st January 2015) - Zhang, He; Vedder, Oscar; Becker, Peter H.; Bouwhuis, Sandra
Abstract : Individual life span is the most important determinant of lifetime reproductive success and fitness across taxa. Identifying the relationships between life‐history traits and survival therefore is fundamental to understanding the evolution of a species' traits. Especially important in this respect is to separate the contributions of between‐ and within‐individual trait effects, because only such an approach can identify markers of individual quality and expose within‐individual processes such as aging or the occurrence of costs of reproduction. Here we report a rigorous cross‐trait comparison in which we quantify effects of between‐ and within‐individual variation in phenology, body mass, and reproductive performance on mortality risk in a long‐lived seabird, the Common Tern Sterna hirundo . Between individuals, earlier arrival at the breeding colony, earlier egg‐laying, greater body mass, and more successful reproduction are associated with a lower mortality risk, and are markers of individual quality. The standardized between‐individual effects of arrival and laying date especially stand out, suggesting that phenology represents the best proxy for life span. In contrast, within individuals, earlier phenology, greater body mass, and more successful reproduction are associated with a higher mortality risk, as is a reduced probability of breeding. After correcting for changes in traits with age, within‐individual effects of phenology, breeding probability, clutch size, and egg volume remain significantly associated with mortality risk, which reveals survival costs of early arrival and initial investment in reproduction, but suggests terminal effects in breeding probability. Overall, our study illustrates the usefulness of separating between‐ and within‐individual trait effects on fitness measures to identify markers of individual quality and life‐history trade‐offs in natural populations.